2021
DOI: 10.3389/fneur.2021.645444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Effect of Cerebral Small Vessel Disease in Stroke Patients With Aspirin Treatment Failure–A Hospital-Based Stroke Secondary Prevention Registry

Abstract: Background: Breakthrough strokes during treatment with aspirin, termed clinical aspirin treatment failure (ATF), is common in clinical practice. The burden of cerebral small vessel disease (SVD) is associated with an increased recurrent ischemic stroke risk. However, the association between SVD and ATF remains unclear. This study investigated the prevalence and clinical characteristics of SVD in stroke patients with ATF.Methods: Data from a prospective, and multicenter stroke with ATF registry established in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…European population-based studies reported overall prevalence ranging from 6.4-15% (25,26). Asian population-based studies reported a prevalence ranging from 3-37% (27,28). Similar vascular risk factors like age, hypertension, higher systolic and diastolic blood pressure, and smoking were associated with the presence of CMBs.…”
Section: Cerebral Microbleedsmentioning
confidence: 91%
See 1 more Smart Citation
“…European population-based studies reported overall prevalence ranging from 6.4-15% (25,26). Asian population-based studies reported a prevalence ranging from 3-37% (27,28). Similar vascular risk factors like age, hypertension, higher systolic and diastolic blood pressure, and smoking were associated with the presence of CMBs.…”
Section: Cerebral Microbleedsmentioning
confidence: 91%
“…Similarly, higher prevalence of SVS (46%), CMBs (53%), and WMHs (93%) was observed in a hospital-based registry in Taiwan. Age and hypertension were among the major associated risk factors ( 29 ).…”
Section: Epidemiology Of Different Types Of Cerebral Small Vessel Dis...mentioning
confidence: 99%